FATAL HEAD INJURY IN MOTOR VEHICLE ACCIDENTS: A DESCRIPTIVE STUDY OF 37 AUTOPSIES - R, Razuin; SA, Rohayu; MS, Mahmood; RI, Krishnan; Ann C, Patricia; PN, Samberkar (Journal of Forensic Medicine and Toxicology, 2011)
Introduction: Road traffic accident related deaths contributed 25 to 35% of all autopsies between 2003 and 2006 at the National Institute of Forensic Medicine (NIFM), Hospital Kuala Lumpur. The causes of death were usually head injury, chest injury, abdominal and multiple injuries. Head injury, by far, was the most common cause of death recorded by the Institute. The objectives of the study were to determine: (a) the demographic characteristics of fatal motor vehicle accident (MVA) victims; (b) category of road users involved in such events; and (c) the causes of death, types of brain damage as well as presence of diffuse axonal injury (DAI) in the study subjects. Methodology: Thirty seven MVA victims were included. The autopsies were conducted at NIFM in August, September and November 2008. Brain samples were collected and analysed histopathologically by Haematoxylin & Eosin and Bielchowsky silver stains. Findings: Malays were the predominant group (46%). Males constituted 95%, with 20 to 30 year-olds being the highest affected age group (46%). Motorcyclists contributed 67.6% of the cases; 92% of the victims succumbed to death almost immediately. All the victims showed presence of brain injury, ranging from cerebral oedema to extensive brain lacerations. Cranio-cerebral injuries were the sole cause of death in 37.8% of the victims; more than 60% sustained other bodily injuries in addition to the head injury.